The Influence of Venture Capital on the Evolution of Payment Strategies in Mergers and Acquisitions: An In-Depth Literature Analysis - Yulianti, Grace; Chaidir, Mohammad; Santoso, Seger (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores the role of venture capital (VC) in shaping payment methods in mergers and acquisitions (M&As). It analyzes the influence of venture capitalists' syndication, investment horizon, and exit strategies on the choice between cash and equity-based payments in M&A transactions. The review finds that VC-backed M&As are more likely to utilize equity-based payment methods, particularly when venture capitalists aim for long-term growth or syndicate deals. Furthermore, macroeconomic conditions and market uncertainty also play a pivotal role in determining payment choices. By synthesizing findings from recent studies, this review enhances the understanding of VC's impact on payment structures in M&As and provides valuable insights for both researchers and practitioners in the field of corporate finance.